Análise da execução penal envolvendo crimes econômicos no Paraná cuja pena privativa de liberdade foi substituída por prestação de serviços e/ou pecuniária - Nickel, Helena (2019)
The main goal of this research was to analyze, based on Becker's theory (1968), the aspects of crime under the socioeconomic circumstances of the illicit practice of convicts in the scope of the 4th Federal Court of Foz do Iguaçu, Judiciary Section of Paraná (Brazil), whose sentences have been replaced by community service and/or pecuniary sanctions. In order to achieve the goal of the research, interviews were carried out through the application of questionnaires to 272 convicted criminals (222 being used for the descriptive analysis and econometric resource – Logit model – aiming to analyze which factors contribute to resocialization of the convicted criminal). The majority of the interviewees were male (86.5%), white (74.8%), in the young age group (between 18 to 33 years old, totalizing 55%), being mostly from the Paraná State (paranaenses). One of the remarkable aspects was the level of formal education, attended middle school (47.3%), with religious practice for 59.5% of respondents, 40.1% were working and receiving income between one and two minimum wages, with smuggled goods (mostly cigarettes) being the most frequent offense (52.7%). The main motivation for economic crime is related to the idea of easy gain/induction of friends/greed, ambition, avarice/envy/maintaining status (46.1%). Regarding the cost-benefit ratio of the criminal activity, 73% of respondents said that the benefit was greater than the cost, contributing for these people to migrating to the illicit. The econometric analysis revealed three variables that contribute positively to the resocialization: the note contained in the report that the entities provide monthly to the federal justice system (chance ratio of 1.350); the adequate service provided with the professional qualification (chance ratio of 3.170); and the risk of punishment by another penalty (higher chance ratio, 5.501). The negative variable was the fear of the criminal organization, showing that the greater the fear, the less is the chance of resocialization (chance ratio of 0.332).